The growth of Halal tourism research and the evidence of Halal hospitality attributes - Luz, Ana Rita Gonçalves (2021)
Halal Tourism is considered one of the fastest-growing markets, however, the literature related to this topic is still scarce. Hence, this study aims to highlight the major contributors to the literature on Halal tourism, both in number of published articles and number of citations, with the goal of mitigating its dispersion and fostering the development of new research. To this end, a systematic literature review was conducted, using the Scopus database, followed by a bibliometric analysis of the selected articles. In addition, the study aims to evidence the Halal attributes most often mentioned as relevant in hospitality, according to Muslim tourists and tourism professionals, through a content analysis of a specific sample of articles. Through this thesis, it was concluded that the literature on Halal tourism has been growing in recent years, both in number of publications and number of citations, and that Halal hospitality attributes have greater relative importance in countries that are members of the Organization of Islamic Cooperation than in non-member countries.